Identification and Differentiation of Polygonum multiflorum Radix and Polygoni multiflori Radix Preaparata through the Quantitative Analysis of Multicomponents by the Single-Marker Method - Ding-Qiang Luo; Pu Jia; Shan-Shan Zhao; Ye Zhao; Hai-Jing Liu; Feng Wei; Shuang-Cheng Ma (Journal of Analytical Methods in Chemistry)
The quantitative analysis of multicomponents by the single-marker (QAMS) method was established and the relationship between F value (the ratio of the sum of the contents of emodin-8-O-β-D-glucopyranoside and physcion-8-O-β-D-glucopyranoside to the sum of the contents of emodin and physcion) and the steaming time was found to identify and differentiate Polygonum multiflorum Radix and its processed product. Emodin was considered as the control substance, and the correction factors of physcion, emodin-8-O-β-D-glucopyranoside, and physcion-8-O-β-D-glucopyranoside were computed. In addition, the contents of the four components were determined. When the F value is greater than or equal to 1.0, the sample was identified as Polygonum multiflorum Radix, and if the F value was between 0.6 and 1.0, the sample of Polygoni multiflori Radix Preaparata was processed incompletely. The F value of the qualified Radix Polygonum multiflorum should be no more than 0.6. However, the influence of different sample injection volumes and the chromatographic columns and instruments used on the durability of the correction factors and RSD ≤3% hindered accurate identification; therefore, a QAMS method using an external standard value with methodological verification was developed. We redefined the “Polygonum multiflorum rules.” The method using “Polygonum multiflorum rules” revised after optimization of the determination results was used, as it was accurate and led to convenient operation and low inspection costs, and moreover, the method could differentiate Polygoni multiflori Radix Preaparata and Polygonum multiflorum Radix medicinal samples and precisely identify samples that were different from the completely processed product Polygoni multiflori Radix Preaparata.